2017
DOI: 10.1007/s40273-017-0570-9
|View full text |Cite
|
Sign up to set email alerts
|

Concordance of Adherence Measurement Using Self-Reported Adherence Questionnaires and Medication Monitoring Devices: An Updated Review

Abstract: Results from our review are consistent with previous studies, as we found that many of our studies produced moderate to high correlation between both SRQs and monitoring devices [Farmer, Clin Ther 21(6):1074-90 (1999), IMS Institute for Healthcare Informatics. Avoidable costs in US health care (2012), Patel et al., Respirology 18(3):546-52 (2013), Siracusa et al., J Cyst Fibros 14(5):621-6 (2015), Smith et al., Int J Cardiol 145(1):122-3 (2010)]. Our findings demonstrate that self-reported adherence produces c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 56 publications
2
53
0
Order By: Relevance
“…Overall, highest correlations could be found for TM ± 30 min. As suggested by previous literature [32], self-reports and EM seem to produce similar results on NA which leads to the conclusion that they measure the same construct. Since the highest accuracy was reached for the strictest measure of NA (TM ± 30 min), it can be assumed that small deviations from the dosing schedule are generally reported by patients.…”
Section: Prevalence Of Non-adherence and Association Of Measurement Msupporting
confidence: 81%
See 1 more Smart Citation
“…Overall, highest correlations could be found for TM ± 30 min. As suggested by previous literature [32], self-reports and EM seem to produce similar results on NA which leads to the conclusion that they measure the same construct. Since the highest accuracy was reached for the strictest measure of NA (TM ± 30 min), it can be assumed that small deviations from the dosing schedule are generally reported by patients.…”
Section: Prevalence Of Non-adherence and Association Of Measurement Msupporting
confidence: 81%
“…Studies on the correlations of EM with other adherence measures show mixed results. In a review on adherence in a general population, a high to moderate concordance between EM and self-reports could be found [32], whereas another review found selfreports to be systematically underestimating NA compared to EM [33]. Studies examining the correlations of different adherence measures in RTRs are sparse.…”
Section: Introductionmentioning
confidence: 99%
“…Recent pharmacokinetic simulation data indicate that AE4 h may be more relevant [40]. However, self-reported adherence is often underreported [17,41,42], which may advocate for continuing the use of AE2 h. To our knowledge, there are no data comparing 2-vs. 4-h time windows on longterm outcomes. *The result is significant with P-value 0.05 or less (2-tailed).…”
Section: Discussionmentioning
confidence: 99%
“…All data were self-reported. However, review articles about the measurement of medication adherence have found moderate-to-high concordance between self-reported patient questionnaires and diaries, and electronic monitoring (Garber et al 2004 ; Shi et al 2010 ; Monnette et al 2018 ). In a study of patients with bipolar disorder, good agreement was found between patient questionnaires and serum levels of psychotropic medications (Jónsdóttir et al 2010 ).…”
Section: Discussionmentioning
confidence: 99%